Keanekaragaman Jenis Ikan di Hilir Sungai Sekadau Kalimantan Barat - Tri Rima Setyawati, Kristoforus Slamet Suryadi Junardi (Jurnal Protobiont, 2019)
Diversity of fish species is important known to determinate river. The purpose of this study was to determine the diversity and distribution of fish also environmental conditions in the lower reaches of the Sekadau River, West Kalimantan. Data collection is conducted from March to May 2018 using posat and gill net. The results showed that the most common Cyprinidae family was found in Rasbora argyrotaenia and Osteochilus microcephalus with dominance value 0.72 and 0.70 respectively.